Food and human evolution : how ancestral diets shaped our minds and bodies - Hudson, Berman D. (Algora Publishing, 2021)
"Food has played a major role in human evolution. The fact that we stand upright, that we can talk, that we have big brains; even traits such as altruism and a sense of fairness - all of these can be attributed largely to the kinds of food our ancestors ate and how they acquired it. We now face a modern food-related crisis. This book describes how the rise of industrial food production during the 20th century unleashed an epidemic of metabolic disease that now threatens the very future of our species"--